Biosynthesis of DNA for disease detection. - Ibrahim, Nur Aifiah Binti (Jurnal Mangifera Edu, 2025)
An aquatic plant breathes through pores in the atmosphere, creating a bacterial loop cycle. Harmful toxins and pathogens invade the foreign substrate and recessive genes. The purpose of this study is gene editing and gene expression containing information to produce proteins and fight back pathogens. The Methodology of this study is the biosphere of RNA involved in the transcription and translation of DNA to detect several diseases. It is a narrative review of DNA biosynthesis in identifying the mutations for genes, chromosomes, or proteins. Genetic alterations in cancer development have urged many researchers to continue their expedition to find prevention strategies and treatments that are curable for the disease. Thus, gene therapies include gene augmentation, gene slicing, gene suicide, and gene editing by treating certain diseases. The momentum of replacing a damaged gene with a healthy gene using gene therapy in treating a wide range of diseases is quite impressive. An inborn child will have a healthy gene by inheriting it from the parent to the infant for further development. Circular RNAs are meant for protein synthesis. The nutrients are the building blocks of amino acids. The regrowth of new tissues is used to rejuvenate organ transplants. It is highly apprehensive for microbial cells to produce on their own. Not all bacteria are good, but the ones that fight off pathogens in the circular loops of plasmids. The DNA of bacterial cells is composed of chromosomal traits of inheritance in providing nutritious meals and becoming an antibody.